Strategies to improve the quality of survival for childhood brain tumour survivors - Tallen, Gesche; Witt, Olaf (European journal of paediatric neurology, 2015)
Background - Tumours of the central nervous system (CNS) are the most frequent solid tumours and the second most frequent type of cancer in children and adolescents. Overall survival has continuously improved in Germany, since an increasing number of patients have been treated according to standardised, multicentre, multimodal treatment recommendations, trials of the German Paediatric Brain Tumour Consortium (HIT-Network) or the International Society of Paediatric Oncology-Europe (SIOP-E) during the last decades. Today, two out of three patients survive. At least 8000 long-term childhood brain tumour survivors (CBTS) are currently living in Germany. They face lifelong disease- and treatment-related late effects (LE) and associated socioeconomic problems more than many other childhood cancer survivors (CCS). - Method - We review the LE and resulting special needs of this particular group of CCS. - Results - Despite their increasing relevance for future treatment optimisation, neither the diversity of chronic and cumulative LE nor their pertinent risk factors and subsequent impact on quality of survival have yet been comprehensively addressed for CBTS treated according to HIT- or SIOP-E-protocols. Evidence-based information to empower survivors and stakeholders, as well as medical expertise to manage their individual health care, psychosocial and educational/vocational needs must still be generated and established. - Conclusion - The establishment of a long-term research- and care network in Germany shall contribute to a European platform, that aims at optimising CBTSs' transition into adulthood as resilient individuals with high quality of survival including optimal levels of activity, participation and acceptance by society.
Gesehen am 29.06.2020